2003
DOI: 10.1002/ijc.10942
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine biosynthesis inhibition enhances HSV‐1 thymidine kinase/ganciclovir‐mediated cytotoxicity in tumor cells

Abstract: Cancer gene therapy with the aid of herpes simplex virus type 1 thymidine kinase gene (HSV-TK) and anti-herpes drug ganciclovir (GCV) has been widely used and its efficacy has been demonstrated in a variety of different malignant cells and animal tumor models. It is also commonly accepted, however, that this gene therapy regimen needs to be enhanced for a true clinical success. We studied whether polyamine biosynthesis inhibition by 2-difluoromethylornithine (DFMO), a clinically tested and well-tolerated chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…As demonstrated in our earlier study, also the 2-difluoromethyl ornithine (DFMO)-induced polyamine biosynthesis inhibition accompanied with a predominant cell cycle arrest can be used to enhance HSV-TK/GCV gene therapy (5). We showed that DFMO caused a long-lasting disturbance to the cell cycle of different tumor cells and a correct timing of DFMO and GCV treatments yielded synergistic cytotoxic effect.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…As demonstrated in our earlier study, also the 2-difluoromethyl ornithine (DFMO)-induced polyamine biosynthesis inhibition accompanied with a predominant cell cycle arrest can be used to enhance HSV-TK/GCV gene therapy (5). We showed that DFMO caused a long-lasting disturbance to the cell cycle of different tumor cells and a correct timing of DFMO and GCV treatments yielded synergistic cytotoxic effect.…”
Section: Introductionmentioning
confidence: 75%
“…In theory, this can be accomplished by arresting the cell population at a certain point of the cell cycle, releasing the block and then destroying the enriched S phase fraction of the cells with HSV-TK/GCV gene therapy. Perhaps the simplest way to introduce transient cell cycle arrest is to use serum deprivation, but our results have shown that increase of the S phase cells is too transient to be synergized with the HSV-TK/GCV gene therapy (5) and certainly this type of approach would not be useful in a clinical setting. Fortunately, there are many drugs available today that can halt cell proliferation at certain point of the cell cycle via different mechanisms.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations